Why do Indonesian Muslims Donate through Crowdfunding Platforms? An Integration of UTAUT, Transparency, and Trust - Novita Nur Hamidah; Frank Aligarh; Ade Setiawan; Usnan Usnan; Faqih Hilmi (International Journal of Islamic Economics and Finance)
Indonesia's recognition as the most charitable country in the world makes research on donations through crowdfunding platforms an intriguing subject for study. The objective of this study is to analyze the impact of technology and institutions factors on people's intentions to donate through the crowdfunding platform. This study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample size of 155 questionnaires. The results indicate that components of Unified Theory of Acceptance and Use of Technology (UTAUT) (performance expectancy, effort expectancy, facilitating conditions, and social influence) and institutional factors (trust and transparency) have a significant positive influence on people's intentions to donate through the platform kitabisa.com. These findings imply the importance of developing new technologies for philanthropic organizations and increasing public intention to donate, especially through donation crowdfunding. This research also contributes theoretically to the development of the UTAUT model by integrating trust and transparency.